Is Problem Solving and Systems Thinking Related? A Case Study in a Malaysian University - Ying, L.; Kheng, F.; Hiong, T.; Goh, K.; Lim, A.; Lee, Elinda (2014)
Does systems thinking facilitate the acquisition of important skills in solving ill-defined problems? This exploratory study seeks to investigate whether an association exists between problem-solving and informal systems-thinking skills. A survey methodology that included a paper and pencil test was used to gather data. Four performance tasks designed and adapted to local context were employed to measure both sets of skills. Following that, the performance of each respondent was scored based on an analytical scoring rubric. Both descriptive and inferential data analysis involving comparisons of the populations and checking for correlations were carried out. Findings indicated that the respondents performed poorly in all the tasks. The mean score for systems thinking was found to be lower than that of problem solving. These skills were analysed according to three preselected demographics. Interestingly, the data indicated that there was a positive but moderate association between problem-solving and systems-thinking skills. The limitations and some general recommendations for future research were also discussed.